Kombucha Cellulose Growth Comparison: Utilizing Branded Tea for Accelerating Architectural Biomaterial Production in Indonesia - Lianto, Fermanto; Trisno, Rudy; Husin, Denny (Engineering And Technology Journal, 2023)
One of the most recent phenomenal biomaterial trends is produced by kombucha. Its cellulose becomes viral once it is experimented on as a synthetic fabric in architectural and fashion products. The uttermost issues still lie on the unstable layer and larger plane production, while most experimentation goes slow on organic processes. Kombucha cellulose production depends on the quality of 3 fundamental materials such as tea, sugar, and water. Growing on the surface of a liquid, the most challenging problem is media sensitivity towards the surrounding environment, as it reflects cellulose productivity. The debates involve a critique of the utilization of high-quality material that generally does not impact the cellulose building, even if producing a more delicious tea. However, the traditional home-brewed technique is still dominant in most places, especially in developing countries like Indonesia. This paper aims to suggest a reasonable material shift in traditional fermentation, especially for improving kombucha cellulose thickness, which is core in biomaterial production. A comparison is presented to compare kombucha cellulose productions using better quality ingredients. The kombucha is fermented under a natural tropic storing environment: a temperature between 26°C-30°C in a dark room and a humidity of 60%. An initiated sugar composition of 10%, a pH between 3-5.5, with final alcohol less than 5%. A variation of mixtures is introduced to verify stable cellulose productivity. A compilation of measurements is taken in 3 consecutive weeks to reveal the growth pattern. The result is a maximal range of thickness growth and a stable and productive layer of kombucha cellulose.